2016
DOI: 10.1007/s10461-016-1470-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Interruption Among HIV Postive People Who Use Drugs in a Setting with a Community-Wide HIV Treatment-as-Prevention Initiative

Abstract: HIV Treatment as Prevention (TasP) initiatives promote antiretroviral therapy (ART) access and optimal adherence (≥95 %) to produce viral suppression among people living with HIV (PLHIV) and prevent the onward transmission of HIV. ART treatment interruptions are common among PLHIV who use drugs and undermine the effectiveness of TasP. Semi-structured interviews were conducted with 39 PLHIV who use drugs who had experienced treatment ART interruptions in a setting with a community-wide TasP initiative (Vancouve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…While requirements of a treatment regimen (e.g., number of pills, health care visits, and dosing restrictions) may increase risk for TRF, other patient characteristics (e.g., social support, quality of life, and cultural beliefs) may serve as protective factors. A recent qualitative study of 39 PLWH who used drugs in Vancouver, Canada underscored the importance of social and structural factors that may underlie the onset of TRF and result in ART treatment interruptions (McNeil et al, 2017). Specifically, prior negative experiences with early and complex ART regimens (e.g., side effects, development of drug resistance) emerged as a perceived factor associated with TRF.…”
mentioning
confidence: 99%
“…While requirements of a treatment regimen (e.g., number of pills, health care visits, and dosing restrictions) may increase risk for TRF, other patient characteristics (e.g., social support, quality of life, and cultural beliefs) may serve as protective factors. A recent qualitative study of 39 PLWH who used drugs in Vancouver, Canada underscored the importance of social and structural factors that may underlie the onset of TRF and result in ART treatment interruptions (McNeil et al, 2017). Specifically, prior negative experiences with early and complex ART regimens (e.g., side effects, development of drug resistance) emerged as a perceived factor associated with TRF.…”
mentioning
confidence: 99%
“…In correctional systems, issues in relation to difficulty accessing HIV medications were reported in two qualitative studies by McNeil et al [66] and Small et al [62] in Canada. In the two studies, some participants complained about the unavailability of HIV medication between the times of arrest, trial and arrival at the institution where they served their sentence, and upon release from custody [62,66]. As such, these structural factors increased the challenge of drug users' access to HIV care.…”
Section: Accessibility and Conditionality Of Hiv And Addiction Treatmentmentioning
confidence: 98%
“…Seven studies reported that HIV-positive drug users/inmates had experienced stigmatization and discrimination associated with HIV and illicit drug use [57,59,61,62,[64][65][66]. Some experienced violence in the prison settings [62] and others were shunned and discriminated against by family [57,[64][65][66], police officers [59] and health professionals [61,65,67] due to their HIV status. In addition to HIV status, participants' engagement in the everyday violence associated with their drug dependence appeared to exacerbate their negative image portrayed by society [66].…”
Section: Stigmatization In Relation To Hiv and Illicit Drug Usementioning
confidence: 99%
See 2 more Smart Citations